Sulfa Drugs as Inhibitors of Carbonic Anhydrase: New Targets for the Old Drugs. (8th September 2014) - al-Rashida, Mariya; Hussain, Sajad; Hamayoun, Mehwish; Altaf, Aisha; Iqbal, Jamshed
Abstract : Sulfa drugs are well-known antibacterial agents containing N-substituted sulfonamide group on para position of aniline ring (NH2 RSO2 NHR′). In this study 2, 4-dichloro-1, 3, 5-triazine derivatives of sulfa drugs, sulfamerazine (1b ), sulfaquinoxaline (2b ), sulfadiazine (3b ), sulfadimidine (4b ), and sulfachloropyrazine (5b ) (1a –5a ) were synthesized and characterized. Their carbonic anhydrase inhibition activity was evaluated against bovine cytosolic carbonic anhydrase isozyme II (bCA II). For the sake of comparison the CA inhibition activity of the parent sulfa drugs (1b –5b ) was also evaluated. A significant increase in CA inhibition activity of sulfa drugs was observed upon substitution with 2, 4-dichloro-1, 3, 5-triazine moiety. Molecular docking studies were carried out to highlight binding site interactions. ADME properties were calculated to evaluate drug likeness of the compounds.